2009
DOI: 10.1111/j.1365-2028.2008.01025.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of aloe mortality with and without elephants in the Thicket Biome of South Africa

Abstract: Studies concerning the influence of African elephants (Loxodonta africana) on vegetation have produced contradictory results; some show minimal or no effect while others report significant elephant-induced effects. Elephants are generalist megaherbivores but will selectively feed from preferred plant species. We investigated the mortality of aloe plants (highly preferred food items for elephants) at five sites with elephants (treatment) and five paired sites without elephants (control) in the Eastern Cape Prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Studies on the impact of elephant browsing on tall single-stemmed aloes have shown that there is generally a higher proportion of dead aloes at sites where elephants are present than control sites where they are absent Bernard, 2008, 2009;Penzhorn et al, 1974). Elephants either break off the aloe's crown, or push the whole plant over to access the succulent apical meristem, both of which usually result in plant death (Parker and Bernard, 2009). Furthermore, Breebart et al (2002) showed that goat browsing has a similar impact on A. ferox, with only 2% of individuals surviving after utilization by Boer goats.…”
Section: Single-stemmed Aloesmentioning
confidence: 97%
See 3 more Smart Citations
“…Studies on the impact of elephant browsing on tall single-stemmed aloes have shown that there is generally a higher proportion of dead aloes at sites where elephants are present than control sites where they are absent Bernard, 2008, 2009;Penzhorn et al, 1974). Elephants either break off the aloe's crown, or push the whole plant over to access the succulent apical meristem, both of which usually result in plant death (Parker and Bernard, 2009). Furthermore, Breebart et al (2002) showed that goat browsing has a similar impact on A. ferox, with only 2% of individuals surviving after utilization by Boer goats.…”
Section: Single-stemmed Aloesmentioning
confidence: 97%
“…Aloes can be important indicator species in particular vegetation types, such as Aloe africana and A. ferox in the Thicket Biome of the Eastern Cape (Parker and Bernard, 2009). When thicket vegetation becomes heavily browsed by livestock or elephants and/or other herbivores, aloes are exposed to further exploitation by herbivores, as well as physical factors such as strong winds that could increase their mortality (D.M.…”
Section: The Functional Roles Of Aloes In Their Associated Ecosystemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The physiognomy of aloes makes them highly susceptible to herbivory (Breebaart, Bhikraj & O'Connor, ; O'Connor, Goodman & Clegg, ; Shackleton & Gambiza, ; Parker & Bernard, , ). For example, indigenous herbivores such as bushbuck, warthogs, vervet monkeys, black rhino, eland, greater kudu, porcupines and chacma baboons have been described to have negative effects on aloe populations (Breebaart, Bhikraj & O'Connor, ; Shackleton & Gambiza, ; Parker & Bernard, , ). Elephants in particular may cause a great deal of damage, and if present at high densities, they can be a major contributor to large declines in aloe populations (Penzhorn, Robbertse & Olivier, ; Barratt & Hall‐Martin, ).…”
Section: Introductionmentioning
confidence: 99%